KONTRIBUSI KUALITAS LAYANAN DAN SUASANA RUMAH MAKAN TERHADAP LOYALITAS KONSUMEN PADA RUMAH MAKAN ROCKET CHICKEN - DWITA NINGSIH, WIWIK (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
The industry competition claims the businessman especially in culinary area to be able to use good strategy and relevant in competition. Any of them which used by Rocket Chicken food court is by giving good service quality and creating the situation which can interest the consumer with the purpose to can understand and fulfill consumer necessities as well as can defend the superiority from business which is undergone. This research is done to know the contribution of service quality and the situation of food court with consumer loyalty to Rocket Chicken in Bungah district of Gresik. This research is descriptive quantitative research. The sample which is used is 93 respondents from the total of member population. The data analyzes technique which is used is analyze double correlation which uses SPSS for Windows verse 16.0 program. Hypothesis testing is undertaken by testing T and testing F. The result of hypothesis testing can be said that the service quality and the situation of food court have a contribution to consumer loyalty whether by partial or simultaneous is proven verifiable. The result of this research shows that the condition of service quality is 74.42% and condition of food court situation is 62.12%, so that can be categorized strong and good. The service quality and food court situation has a contribution significant with consumer loyalty. The variable of independent in this research give contribution 52.9% with the consumer loyalty and the remainder is 47.1% influenced the variable outside research. Key word: service quality, food court situation, consumer loyalty.